Method for preparing battery negative-grade hard carbon material using wind turbine blade

CN121672488BActive Publication Date: 2026-08-21SHANGHAI POWER BATTERY RECYCLING CENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610024546.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-09
Publication Date
2026-08-21
Estimated Expiration
2046-01-09

AI Technical Summary

Technical Problem

[0003]废旧风力发电机叶片使用的树脂材料通常为热固性塑料,无法再熔或重塑,具有较大的回收难度

Benefits of technology

[0017](1)本公开的一种利用风力发电机叶片制备电池负级硬碳材料的方法,

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121672488B_ABST
    Figure CN121672488B_ABST
Patent Text Reader

Abstract

The utility model discloses a kind of methods for preparing battery negative grade hard carbon material with wind turbine blade, belong to generator blade material recycling field, comprising: (1) wind turbine blade powder carbonization treatment is carried out, to obtain hard carbon mixture;Wherein, the wind turbine blade powder is the powder formed by crushing glass fiber reinforced resin type blade.(2) the hard carbon mixture is pickled to remove impurities, to obtain battery negative grade hard carbon material.The utility model can recycle wind turbine blade to prepare battery negative grade hard carbon material, and wind turbine blade can be effectively recycled and reused.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure pertains to the field of generator blade material recycling, specifically relating to a method for preparing hard carbon materials for battery negative electrodes using wind turbine blades. Background Technology

[0002] Wind turbines are the primary means of utilizing wind energy, and wind turbine blades are typically made of glass fiber reinforced resin. Because wind turbine blades operate in harsh outdoor environments for extended periods, and given their widespread use, a large number of wind turbine blades will become obsolete in the future. Therefore, it is necessary to develop efficient, environmentally friendly, and low-cost methods for recycling wind turbine blades.

[0003] The resin materials used in spent wind turbine blades are typically thermosetting plastics, which cannot be melted or remolded, making recycling quite difficult. Current recycling methods involve oxidizing and pyrolyzing the resin to remove the glass fibers. However, this process generates large amounts of waste gas, causing severe pollution, thus reducing the economic value of recycling the glass fibers. Consequently, there is a lack of technologies that can efficiently recycle wind turbine blades for reuse. Summary of the Invention

[0004] In view of the shortcomings of the prior art described above, the purpose of this disclosure is to provide a method for preparing hard carbon materials for battery negative electrodes using wind turbine blades, which can recycle wind turbine blades to prepare hard carbon materials for battery negative electrodes, and can effectively recycle and reuse wind turbine blades.

[0005] This disclosure provides a method for preparing hard carbon materials for battery negative electrodes using wind turbine blades, including:

[0006] The wind turbine blade powder is carbonized to obtain a hard carbon mixture; wherein the wind turbine blade powder is powder formed by crushing glass fiber reinforced resin blades; and the hard carbon mixture is acid-washed to remove impurities to obtain a battery negative electrode hard carbon material.

[0007] According to some embodiments of this disclosure, the pickling process includes: pickling the hard carbon mixture with a first acid solution to remove silicon dioxide, obtaining a preliminary pickling product; and pickling the preliminary pickling product with a second acid solution to remove metal impurities, obtaining the battery negative electrode hard carbon material.

[0008] According to some embodiments of this disclosure, the first acid solution is a hydrofluoric acid solution, wherein the concentration of the hydrofluoric acid is 8-40 wt%, the temperature is 40-80°C, and the time is 6-24 h.

[0009] According to some embodiments of this disclosure, the second acid solution is a hydrochloric acid solution, wherein the concentration of the hydrochloric acid is 12-37 wt%, the temperature is 80-120°C, and the time is 4-12 h.

[0010] According to some embodiments of this disclosure, the carbonization process includes: subjecting the wind turbine blade powder to Joule heating treatment under an inert atmosphere.

[0011] According to some embodiments of this disclosure, the Joule heating treatment is performed at a temperature of 700-1600°C for 5-10 minutes.

[0012] According to some embodiments of this disclosure, the heating temperature of the Joule heating treatment is 900-1600°C.

[0013] According to some embodiments of this disclosure, the particle size of the powder particles in the wind turbine blade powder is less than 80 mesh.

[0014] According to some embodiments of this disclosure, it further includes: high-energy ball milling of the battery negative electrode hard carbon material to the micrometer level and below.

[0015] According to some embodiments of this disclosure, the high-energy ball milling process includes: using a high-energy ball mill to ball mill the battery negative electrode hard carbon material at a speed of 800-1000 rpm for 30 minutes, and repeating the cycle 8-12 times.

[0016] Beneficial effects:

[0017] (1) A method for preparing hard carbon material for battery negative electrode using wind turbine blades disclosed herein.

[0018] First, wind turbine blade powder is carbonized to obtain a hard carbon mixture. Then, impurities in the hard carbon mixture are removed by acid washing to obtain a high-purity battery negative electrode hard carbon material with a rich pore structure. Compared with the traditional method of recycling glass fiber from wind turbine blades, the battery negative electrode hard carbon material recovered in this disclosure has higher economic and application value.

[0019] (2) The present invention discloses a method for preparing hard carbon material for battery negative electrode using wind turbine blades. The wind turbine blade powder is pyrolyzed by Joule heating. The Joule heating reaction time is much shorter than that of traditional tube furnace heating, which greatly saves process time, improves production efficiency, and helps to reduce impurities.

[0020] (3) The present invention discloses a method for preparing battery negative hard carbon material using wind turbine blades. The battery negative hard carbon material with small particle size is obtained by high-energy ball milling. Compared with the battery negative hard carbon material prepared with biomass as a precursor, it has a smaller particle size and higher purity, thus exhibiting good conductivity.

[0021] (4) The present invention discloses a method for preparing hard carbon material for battery negative electrode using wind turbine blades. Due to the cross-linked structure of the precursor resin after carbonization, the microstructure of the hard carbon material for battery negative electrode has disordered graphite-like layers, abundant edge and surface defects and abundant pore structure. When applied to the negative electrode of sodium-ion battery, sodium-ion battery exhibits a high specific capacity.

[0022] (5) The present invention discloses a method for preparing hard carbon material for battery negative electrode using wind turbine blades, which can be used as a battery negative electrode material in scenarios such as energy storage power stations, low-speed electric vehicles and electric bicycles, and is conducive to the promotion and utilization of clean energy. Attached Figure Description

[0023] Figure 1 This is a flowchart of a method for preparing hard carbon materials for battery negative electrodes using wind turbine blades.

[0024] Figure 2 This is a schematic diagram of the hard carbon material for the sodium-ion battery negative electrode prepared in Example 1.

[0025] Figure 3 This is an X-ray diffraction pattern of the hard carbon material for the sodium-ion battery negative electrode prepared in Example 1.

[0026] Figure 4 This is a high-resolution transmission electron microscope image of the hard carbon material for the sodium-ion battery negative electrode prepared in Example 1.

[0027] Figure 5 This is a scanning electron microscope image of the hard carbon material for the sodium-ion battery negative electrode prepared in Example 1.

[0028] Figure 6 This is a high-angle annular dark-field scanning transmission atomic image of the hard carbon material for sodium-ion battery anode prepared in Example 1.

[0029] Figure 7 This is the energy dispersive X-ray spectrum of the hard carbon material for the sodium-ion battery negative electrode prepared in Example 1.

[0030] Figure 8 This is a dQ / dV curve of a sodium-ion button battery made using the hard carbon material prepared in Example 1 as the negative electrode.

[0031] Figure 9 A sodium-ion button cell was fabricated using the hard carbon material prepared in Example 1 as the negative electrode. The battery operates at 1 Ag. -1 Voltage-specific capacity curve at current density.

[0032] Figure 10This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Example 1 as the anode.

[0033] Figure 11 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Example 2 as the anode.

[0034] Figure 12 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Example 3 as the anode.

[0035] Figure 13 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Example 4 as the anode.

[0036] Figure 14 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Example 5 as the anode.

[0037] Figure 15 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Example 6 as the anode.

[0038] Figure 16 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Example 7 as the anode.

[0039] Figure 17 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Example 8 as the anode.

[0040] Figure 18 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Comparative Example 1 as the anode.

[0041] Figure 19 This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Comparative Example 2 as the anode.

[0042] Figure 20This is a schematic diagram of the number of cycles and specific capacity of a sodium-ion button battery made using the hard carbon material of sodium-ion battery anode prepared in Comparative Example 3 as the anode. Detailed Implementation

[0043] The following specific examples illustrate the implementation of this disclosure. Those skilled in the art can easily understand other advantages and effects of this disclosure from the information disclosed herein. This disclosure can also be implemented or applied through other different specific embodiments, and various details in this disclosure can be modified or changed according to different viewpoints and application modules without departing from the spirit of this disclosure. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this disclosure can be combined with each other.

[0044] The embodiments of this disclosure will now be described in detail with reference to the accompanying drawings, so that those skilled in the art to which this disclosure pertains can readily implement it. This disclosure may be embodied in many different forms and is not limited to the embodiments described herein.

[0045] In this disclosure, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic represented in connection with that embodiment or example is included in at least one embodiment or example of this disclosure. Furthermore, the specific features, structures, materials, or characteristics represented may be combined in any suitable manner in any one or a group of embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples represented in this disclosure, as well as the features of those different embodiments or examples.

[0046] Furthermore, the terms "first" and "second" are used for illustrative purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the representation of this disclosure, "a set" means two or more, unless otherwise explicitly specified.

[0047] For the purpose of clarity, devices unrelated to the description are omitted, and the same or similar components throughout the specification are given the same reference numerals.

[0048] Throughout this specification, when it is said that a device is "connected" to another device, this includes not only "direct connection" but also "indirect connection" by placing other components in between. Furthermore, when it is said that a device "comprises" a certain constituent element, unless otherwise stated otherwise, this does not exclude other constituent elements, but rather implies that other constituent elements may be included.

[0049] While the terms first, second, etc., are used in some examples herein to refer to various elements, these elements should not be limited by these terms. These terms are used only to distinguish one element from another. For example, first interface and second interface, etc., are used. Furthermore, as used herein, the singular forms “a,” “an,” and “the” are intended to also include the plural forms unless the context indicates otherwise. It should be further understood that the terms “comprising,” “including,” indicate the presence of the stated feature, step, operation, element, module, item, kind, and / or group, but do not exclude the presence, occurrence, or addition of one or more other features, steps, operations, elements, modules, items, kinds, and / or groups. The terms “or” and “and / or” as used herein are interpreted as inclusive, or mean any one or any combination thereof. Thus, “A, B, or C” or “A, B, and / or C” means “any one of: A; B; C; A and B; A and C; B and C; A, B, and C.” Exceptions to this definition will only occur if the combination of elements, functions, steps, or operations is inherently mutually exclusive in some way.

[0050] The technical terms used herein are for reference only to specific embodiments and are not intended to limit the scope of this disclosure. The singular form used herein includes the plural form unless the statement explicitly indicates otherwise. The word "comprising" as used in this specification means to specify a particular characteristic, region, integer, step, operation, element, and / or component, and does not exclude the presence or addition of other characteristics, regions, integers, steps, operations, elements, and / or components.

[0051] Although not explicitly defined, all terms, including technical and scientific terms used herein, shall have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. Terms defined in commonly used dictionaries shall be further interpreted as having a meaning consistent with the relevant technical literature and the message of the present disclosure, and shall not be over-interpreted as having an ideal or overly formulaic meaning unless otherwise defined.

[0052] There is a lack of methods in related technologies for the efficient recycling and reuse of wind turbine blades. Therefore, this disclosure provides a method for preparing hard carbon materials for battery negative ions using wind turbine blades, enabling the efficient recycling and reuse of wind turbine blades.

[0053] Figure 1 This is a flowchart of a method for preparing hard carbon materials for battery negative electrodes using wind turbine blades, as disclosed in this publication. (See also...) Figure 1 This disclosure discloses a method for preparing hard carbon materials for battery negative electrodes using wind turbine blades, comprising:

[0054] (1) Carbonize the wind turbine blade powder to obtain a hard carbon mixture; wherein the wind turbine blade powder is powder formed by crushing glass fiber reinforced resin blades.

[0055] The glass fiber reinforced resin blade is made of glass fiber reinforced resin material, which includes resin material and glass fiber reinforcing material. The main component of the resin material is thermosetting resin (epoxy resin). The glass fiber reinforcing material includes silicon dioxide and metal compounds. The metal compounds include aluminum oxide, calcium carbonate, and magnesium oxide, etc., and the content of silicon dioxide is much greater than the content of the metal compounds.

[0056] Thus, during the carbonization process, the resin material participates in the carbonization reaction, undergoes thermal decomposition, removal of volatile components (removal of volatile components generated by water vapor, carbon monoxide, and carbon dioxide), aromatization, and condensation, thereby generating a hard carbon material with a three-dimensional porous structure and mixed with impurities, which serves as a hard carbon mixture.

[0057] Optionally, the glass fiber reinforced resin blades are pulverized to obtain the wind turbine blade powder. The pulverization process includes cutting, crushing, ball milling, and sieving the wind turbine blades. The ball milling, specifically using a planetary ball mill at 300-400 rpm for 2-4 hours, is beneficial for obtaining wind turbine blade powder with a smaller particle size.

[0058] Optionally, the sieve selected for sieving is 80 mesh. Therefore, the particle size of the powder in the wind turbine blade powder obtained after sieving is less than 80 mesh. Each component (resin material, silica, and metal compound) is fully exposed, ensuring that subsequent components can fully participate in the reaction.

[0059] Optionally, the carbonization process includes Joule heating treatment of the wind turbine blade powder under an inert atmosphere. The Joule heating treatment is performed using a Joule heating device with a heating rate of 1000~10000℃ / s. This rapid heating rate facilitates quickly reaching the required carbonization temperature, shortening the carbonization time and improving the preparation efficiency of the hard carbon mixture. Furthermore, the rapid heating allows intermediate products during the carbonization reaction to quickly generate volatile components (water vapor, carbon monoxide, and carbon dioxide, etc.) and volatilize, resulting in a hard carbon material with a rich pore structure.

[0060] Optionally, the Joule heating treatment is performed at a temperature of 700-1600℃ for 5-10 minutes, that is, the wind turbine blade powder is heated at a temperature of 700-1600℃ for 5-10 minutes using the Joule heating method. For example, the heating temperature can be implemented as 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃, 1550℃, or 1600℃.

[0061] Preferably, the Joule heating treatment is performed at a temperature of 900-1600℃. At this temperature, the calcium carbonate metal compound in the glass fiber is thermally decomposed, i.e., calcium carbonate decomposes to produce calcium oxide and carbon dioxide. The volatilization of carbon dioxide is beneficial to reducing impurities in the resulting hard carbon material, facilitating the purification of the hard carbon material, and promoting the formation of a rich pore structure in the hard carbon material.

[0062] Optionally, the inert atmosphere may be argon or an argon-hydrogen mixture.

[0063] (2) The hard carbon mixture is acid-washed to remove impurities, and the battery negative electrode hard carbon material is obtained.

[0064] Optionally, the pickling process includes the following steps: (2.1) pickling the hard carbon mixture with a first acid solution to remove silicon dioxide, obtaining a preliminary pickling product. (2.2) pickling the preliminary pickling product with a second acid solution to remove metal impurities, obtaining the battery negative electrode hard carbon material.

[0065] Understandably, compared to other pickling methods, such as pickling to remove metal impurities first and then pickling to remove silica, or pickling to remove both metal impurities and silica simultaneously, the main reason for this disclosure to pickle silica first and then pickle to remove metal impurities is that, for glass fiber reinforced resin materials, the silica content is much greater than the metal compound content, and silica does not participate in the reaction during the carbonization process. Therefore, in the resulting hard carbon mixture, the silica impurity content is much greater than the metal impurity content. This disclosure removes the more abundant silica impurities first, which is beneficial for exposing more pores and more metal impurities in the resulting hard carbon material after one pickling. This allows the second acid solution to contact the metal impurities more fully during pickling, thus ensuring that the metal impurities are also fully removed. Therefore, the above-mentioned acid washing method is conducive to the thorough removal of silicon dioxide and metal impurities in the hard carbon mixture, so that the hard carbon material of the battery negative electrode obtained after acid washing can expose more pores and have a larger specific surface area. Thus, when it is used to make the negative electrode of sodium-ion battery, it can provide more abundant surface adsorption and insertion sites for sodium ions, and can effectively withstand the volume strain caused by repeated insertion and extraction of sodium ions. This is beneficial to the sodium-ion battery with high specific capacity, excellent rate performance and long cycle life.

[0066] Optionally, the first acid solution is a hydrofluoric acid solution. Hydrofluoric acid can react with silicon dioxide to generate silicon tetrafluoride gas and water, thereby removing silicon dioxide from the hard carbon material and forming more abundant pores.

[0067] Of course, it is understood that the first acid solution in the embodiments of this disclosure includes, but is not limited to, this, and other acid solutions that can corrode silicon dioxide without generating solid impurities are also applicable to this disclosure.

[0068] Optionally, the concentration of the hydrofluoric acid is 8-40 wt%, the temperature is 40-80°C, and the time is 6-24 h.

[0069] As an example, the hydrofluoric acid pickling treatment includes: heating and immersing the hard carbon mixture in hydrofluoric acid, washing with water until the pH value is higher than 6.5, and then filtering out the filter residue as the preliminary pickling product. The concentration of the hydrofluoric acid is 8-40 wt%, the heating and immersion temperature is 40-80°C, and the immersion time is 6-24 hours. As an example, the concentration of the hydrofluoric acid can be implemented as 8-15 wt%, 15-20 wt%, 20-25 wt%, 25-30 wt%, 30-35 wt%, and 35-40 wt%.

[0070] It is worth noting that the concentration of hydrofluoric acid is maintained within the range of 8-40 wt%. This is mainly because when the concentration of hydrofluoric acid is below 8 wt%, its corrosiveness is relatively weak, which is not conducive to the complete removal of silica by the hydrofluoric acid. Furthermore, hydrofluoric acid concentrations above 40 wt% are highly corrosive to equipment and are difficult to obtain, affecting the safety and cost of the hydrofluoric acid pickling treatment.

[0071] Heating and soaking are beneficial for promoting the full reaction between hydrofluoric acid and silica, and for the complete removal of silica.

[0072] Optionally, the second acid solution is a hydrochloric acid solution. The hydrochloric acid solution can react with metallic impurities (calcium oxide, aluminum oxide, and magnesium oxide, etc.) causing the metallic impurities to dissolve in the acidic solution, thereby removing the metallic impurities from the hard carbon material. Of course, it is understood that the first acid solution in the embodiments of this disclosure includes, but is not limited to, this; other acidic solutions capable of corroding metallic impurities without generating solid impurities are also applicable to this disclosure.

[0073] Optionally, the concentration of the hydrochloric acid is 12-37 wt%, the temperature is 80-120℃, and the time is 4-12 h.

[0074] As an example, the hydrochloric acid pickling process includes: heating and soaking the preliminary pickling product in hydrochloric acid, washing it with water until the pH value is higher than 6.5, and then filtering out the filter residue as the hard carbon material for the negative electrode of the battery.

[0075] The concentration of hydrochloric acid is 12-37 wt%, the heating and soaking temperature is 80-120°C, and the soaking time is 4-12 h. For example, the concentration of hydrochloric acid can be implemented as 12-17 wt%, 18-22 wt%, 23-24 wt%, 25-29 wt%, 30-34 wt%, and 35-37 wt%.

[0076] It is worth noting that the concentration of hydrochloric acid is maintained within the range of 12-37 wt%. This is mainly because when the concentration of hydrochloric acid is below 12 wt%, its acidity is relatively weak, which is not conducive to the full reaction between the hydrochloric acid and metallic impurities (calcium oxide, aluminum oxide, and magnesium oxide, etc.). Furthermore, hydrochloric acid concentrations above 37 wt% are highly corrosive to equipment and difficult to obtain, affecting the safety and cost of the hydrochloric acid pickling process. Of course, it is understood that the second acid solution in the embodiments of this disclosure includes, but is not limited to, this; other acidic solutions capable of corroding without affecting hard carbon materials are also applicable to this disclosure.

[0077] Heating and soaking are beneficial for promoting the full reaction between hydrochloric acid and metal impurities, thus facilitating the complete removal of metal impurities.

[0078] (3) The hard carbon material for the battery negative electrode is processed by high-energy ball milling to the micrometer level or below to refine the hard carbon material and obtain a sodium-ion battery negative electrode hard carbon material with small particle size that can be directly used as the negative electrode of a sodium-ion battery. Optionally, the hard carbon material for the sodium-ion battery negative electrode is less than or equal to 300 mesh. Therefore, the high-energy ball milling has a high rotation speed, which can produce hard carbon material with a small particle size. The sodium-ion battery negative electrode prepared with this material is not easy to crack, and its mechanical properties can be guaranteed.

[0079] It is also worth mentioning that the reason why the battery negative electrode hard carbon material is ball-milled after acid washing is that after acid washing removes impurities, the resulting battery negative electrode hard carbon material has more pores and is easier to be ball-milled into smaller particle sizes. This helps to ensure that the hard carbon material finally produced has a smaller particle size with lower energy consumption.

[0080] Optionally, the high-energy ball milling process includes milling the hard carbon material for the battery negative electrode using a high-energy ball mill at a speed of 800-1000 rpm for 30 minutes, and repeating the cycle 8-12 times. For example, using a high-energy ball mill at 800 rpm, rotating clockwise for 15 minutes, pausing for 5 minutes, then rotating counterclockwise for 15 minutes, and repeating the above steps 8-12 times, to obtain a hard carbon material for the sodium-ion battery negative electrode that can be directly used to prepare the negative electrode of a sodium-ion battery.

[0081] Example 1:

[0082] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0083] (2) The wind turbine blade powder was rapidly heated to 1200℃ in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0084] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 40wt% and a temperature of 60℃ for 12h, then washed with water until the pH value was greater than 6, and filtered to obtain filter residue as the initial acid washing product.

[0085] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 37wt% and a temperature of 120℃ for 6 hours, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0086] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0087] Figure 2 This is a schematic diagram of the sodium-ion battery anode hard carbon material prepared in Example 1 placed on the sample stage. The black area represents the sodium-ion battery anode hard carbon material. As can be seen from the figure, the prepared sodium-ion battery anode hard carbon material has a small particle size and uniformity, which is beneficial for preparing a sodium-ion battery anode that is not easy to crack and has excellent mechanical properties.

[0088] Figure 3 The image shows the X-ray diffraction pattern of the sodium-ion battery anode hard carbon material prepared in Example 1. As can be seen from the image, the prepared sodium-ion battery anode hard carbon material exhibits a broad peak in the range of 18-37° without any sharp diffraction peaks, indicating that it has an amorphous structure, which is consistent with the hard carbon material of the battery anode.

[0089] Figure 4 This is a high-resolution transmission electron microscope image of the sodium-ion battery anode hard carbon material prepared in Example 1. As can be seen from the image, the prepared sodium-ion battery anode hard carbon material has lattice fringes with different directions and arrangements, forming disordered graphite-like sheets, further proving that an amorphous structure was obtained, which is consistent with the battery anode hard carbon material.

[0090] Figure 5 This is a scanning electron microscope image of the hard carbon material for the negative electrode of a sodium-ion battery prepared in Example 1. As can be seen from the image, the hard carbon material for the negative electrode of the battery is evenly distributed within the image area.

[0091] Figure 6This is a high-angle annular dark-field scanning transmission atomic image (HAADF-STEM image) of the sodium-ion battery anode hard carbon material prepared in Example 1. As can be seen from the image, the sodium-ion battery anode hard carbon material is composed of a large number of tiny clusters with a diameter of about 5 nm, and these clusters further agglomerate to form a continuous, interpenetrating three-dimensional porous network. This structure brings excellent performance to the sodium-ion battery anode hard carbon material of this disclosure, mainly as follows: (1) Significantly increased sodium storage sites: This structure creates an extremely high specific surface area and abundant lattice edges / defects, providing a large number of surface adsorption and insertion sites for sodium ions. At the same time, the three-dimensional interconnected channels ensure that the electrolyte and sodium ions can fully reach these sites and be efficiently utilized, which directly leads to the high reversible specific capacity of the material. (2) Excellent ion and electron transport dynamics: The 5 nm primary clusters greatly shorten the diffusion path of sodium ions in the solid phase, while the three-dimensional network composed of clusters provides a fast transport channel for ions, significantly reducing the polarization of the electrode, so that the material of this disclosure can still maintain high capacity even under high rate (high current) charge and discharge conditions. (3) Excellent structural stability: During charge and discharge, the pores around the nanoclusters effectively buffer the volume strain caused by sodium ion insertion / extraction, while the robust cluster interconnection structure ensures the overall integrity of the electrode, endowing the material of this disclosure with excellent cycle stability, enabling it to withstand long-term cycling. In summary, Figure 6 The unique microstructure exhibited helps ensure that the sodium-ion battery anode hard carbon material disclosed herein possesses excellent properties such as high capacity, superior rate performance, and long cycle life.

[0092] Figure 7 This is the energy dispersive X-ray spectrum of the sodium-ion battery anode hard carbon material prepared in Example 1. The upper left area of ​​the figure represents the original morphology of the hard carbon material. The areas marked with C, O, and Cu in the figure represent the distribution of C, O, and Cu elements under X-rays. As can be seen from the figure, the main component of the prepared sodium-ion battery anode hard carbon material is carbon, with a very small amount of oxygen and copper elements evenly distributed. The oxygen element comes from a small number of oxygen-containing groups on the surface of the hard carbon, and the copper element comes from the copper substrate of the sample stage on which the sodium-ion battery anode hard carbon material is placed. The glass fiber in the prepared sodium-ion battery anode hard carbon material has been fully removed, and there are few impurities.

[0093] The sodium-ion battery anode hard carbon material obtained in Example 1 was used to prepare a sodium-ion button cell anode and tested using the following method, including the following steps:

[0094] The sodium-ion battery negative electrode hard carbon material prepared in Example 1 was mixed with conductive agent acetylene black and binder (CMC, sodium carboxymethyl cellulose) at a mass ratio of 80:10:10. Then, an appropriate amount of ultrapure water was added as a solvent and the mixture was stirred thoroughly. The resulting slurry was coated on aluminum foil and dried at 120°C for 10 hours under vacuum. Then, a 14 mm diameter disc was punched out using a punching machine. The disc was then compacted under 10 MPa to obtain the button cell negative electrode sheet.

[0095] Commercial sodium vanadium fluorophosphate was mixed with conductive agent acetylene black and binder (PVDF, polyvinylidene fluoride) in a mass ratio of 80:10:10. Then, an appropriate amount of NMP (N-methylpyrrolidone) was added as a solvent and stirred thoroughly. The mixture was coated on aluminum foil and dried at 120°C under vacuum for 10 hours. The resulting disc was then punched out with a diameter of 14 mm using a punching machine to obtain the positive electrode sheet of a button cell.

[0096] In an argon-filled glove box, using 1 mol / L NaPF6 DME as the electrolyte and glass fiber (GF / A) as the separator, and using the above-prepared coin cell positive and negative electrodes as the positive and negative electrodes, coin cells were fabricated according to the coin cell assembly sequence, and constant current charge-discharge tests of 0.01–2.5 V were conducted on the fabricated coin cells at room temperature.

[0097] Figure 8 This is a dQ / dV curve of a sodium-ion button battery made using the hard carbon material prepared in Example 1 as the negative electrode. Figure 9 A sodium-ion button cell was fabricated using the hard carbon material prepared in Example 1 as the negative electrode. The battery measured at 1 A g... -1 Voltage-specific capacity curve at current density. See also... Figures 8-9 The sodium-ion button battery produced has a capacity of 350 mAh g. -1 The cycle specific capacity is at a relatively high level among hard carbon materials for the negative electrode of commercial sodium-ion batteries. Furthermore, the fabricated sodium-ion button cell exhibits a stable voltage plateau within the range of 0.1–0.25V during charging and a stable voltage plateau within the range of 0.2–0.05V during discharging, demonstrating both a stable voltage plateau and high specific capacity.

[0098] Figure 10 This is a schematic diagram illustrating the cycle performance of a sodium-ion button battery fabricated using the hard carbon material prepared in Example 1 as the negative electrode at a high current density of 2 A / g. (See also...) Figure 10The sodium-ion button battery produced exhibited excellent electrochemical stability after the initial cycle. Specifically, after the initial activation process, its specific capacity not only did not decay, but also showed a steady upward trend, and entered a highly stable plateau period from around the 30th cycle. Until the 100th cycle, the specific capacity was still maintained at a high level of about 338 mAh / g, showing an extremely low capacity decay rate.

[0099] These test results clearly demonstrate that the hard carbon material for sodium-ion battery anodes provided in this disclosure possesses a rich porous structure and an extremely high specific surface area. Therefore, the sodium-ion coin cells fabricated from this material exhibit excellent structural stability and can effectively withstand the volumetric strain caused by repeated insertion and extraction of sodium ions. Furthermore, the material maintains high reversible capacity even under high-rate conditions, proving its rapid ion transport kinetics. Thus, the material of this disclosure achieves a balance between high specific capacity, excellent rate performance, and long cycle life.

[0100] Example 2:

[0101] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0102] (2) The wind turbine blade powder was rapidly heated to 1200℃ in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0103] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 20wt% and a temperature of 60℃ for 12h, then washed with water until the pH value was greater than 6, and filtered to obtain filter residue as the initial acid washing product.

[0104] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 25wt% and a temperature of 80℃ for 6 hours, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0105] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0106] The sodium-ion battery anode hard carbon material obtained in Example 2 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1. The cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Example 2 at a high current density of 2 A / g was then tested. Figure 11As shown, under the Joule heating temperature (1200°C) and acid washing conditions used in Example 2, the prepared coin cell exhibited extremely high initial discharge specific capacity, reaching 380.6 mAh / g in the first cycle. Furthermore, after initial activation and structural adjustment, its specific capacity showed a continuous and significant upward trend, stabilizing at a high level of approximately 365 mAh / g after 100 cycles.

[0107] Example 3:

[0108] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0109] (2) The wind turbine blade powder was rapidly heated to 1200℃ in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0110] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 30wt% and a temperature of 80℃ for 24h, then washed with water until the pH value was greater than 6, and filtered to obtain filter residue as the initial acid washing product.

[0111] (4) The initial pickling product is heated in hydrochloric acid with a concentration of 30wt% and a temperature of 120℃ for 12 hours, washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0112] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0113] The sodium-ion battery anode hard carbon material obtained in Example 3 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1. The cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Example 3 at a high current density of 2 A / g was tested. Figure 12 As shown, in Example 3, more intense acid washing conditions (high concentration, high temperature, long time) were explored at the standard high pyrolysis temperature. After the initial deep activation, the specific capacity of the coin cell steadily recovered and increased, eventually stabilizing at about 338 mAh / g.

[0114] Example 4:

[0115] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0116] (2) The wind turbine blade powder was rapidly heated to 1600℃ in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0117] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 10wt% and a temperature of 60℃ for 6 hours, then washed with water until the pH value was greater than 6, and filtered to obtain filter residue as the initial acid washing product.

[0118] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 20wt% and a temperature of 100℃ for 4 hours, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0119] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0120] The sodium-ion battery anode hard carbon material obtained in Example 4 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1. The cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Example 4 was tested at a high current density of 2 A / g. Figure 13 As shown, Example 4 uses an extremely high Joule temperature (1600°C) to utilize the volatilization / conversion of impurities by high temperature, which simplifies the acid washing step (shortening the time and appropriately reducing the concentration). The resulting coin cells exhibit a strong specific capacity growth trend in the later stages of cycling, eventually reaching approximately 335 mAh / g, demonstrating the potential of the high-temperature pathway in simplifying subsequent purification steps and improving production efficiency.

[0121] Example 5:

[0122] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0123] (2) The wind turbine blade powder was rapidly heated to 1400℃ in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0124] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 15wt% and a temperature of 70℃ for 10h, then washed with water until the pH value was greater than 6, and filtered to obtain filter residue as the initial acid washing product.

[0125] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 22wt% and a temperature of 110℃ for 5 hours, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0126] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0127] The sodium-ion battery anode hard carbon material obtained in Example 5 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1. The cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Example 5 at a high current density of 2 A / g was tested. Figure 14 As shown, Example 5 employs a moderate pyrolysis temperature (1400℃) and acid washing intensity, representing a comprehensive optimization. The resulting coin cell exhibits an extremely flat and stable cycling curve, with the specific capacity consistently maintained at a high level of approximately 338 mAh / g and negligible capacity decay, achieving an optimal balance between specific capacity and stability.

[0128] Example 6:

[0129] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0130] (2) The wind turbine blade powder was rapidly heated to 1000℃ in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0131] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 12wt% and a temperature of 50℃ for 15h, then washed with water until the pH value was greater than 6, and the filter residue was obtained by suction filtration as the initial acid washing product.

[0132] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 18wt% and a temperature of 90℃ for 8 hours, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0133] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0134] The sodium-ion battery anode hard carbon material obtained in Example 6 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1, and the cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Example 6 was tested at a high current density of 2 A / g. Figure 15 As shown, Example 6 uses a relatively mild pyrolysis temperature (1000°C) and acid washing conditions, and the specific capacity of the resulting coin cell slowly decreases from about 352 mAh / g initially to about 285 mAh / g after 100 cycles, indicating that under a mild overall process, it is still possible to prepare a hard carbon anode with performance superior to conventional materials.

[0135] Example 7:

[0136] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0137] (2) The wind turbine blade powder was rapidly heated to 700°C in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0138] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 8wt% and a temperature of 40℃ for 18h, then washed with water until the pH value was greater than 6, and the filter residue was obtained by suction filtration as the initial acid washing product.

[0139] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 12wt% and a temperature of 80℃ for 10h, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0140] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0141] The sodium-ion battery anode hard carbon material obtained in Example 7 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1, and the cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Example 7 was tested at a high current density of 2 A / g. Figure 16As shown, Example 7 uses a lower Joule pyrolysis temperature (700°C) and mild acid washing, resulting in a coin cell with a relatively low reversible capacity, with a specific capacity of about 313 mAh / g after 100 cycles. However, the cycling curve is very stable, indicating that an excessively low pyrolysis temperature may limit the specific capacity, but the material still has good structural stability.

[0142] Example 8:

[0143] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0144] (2) The wind turbine blade powder was rapidly heated to 900°C in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0145] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 18wt% and a temperature of 60℃ for 14h, then washed with water until the pH value was greater than 6, and filtered to obtain filter residue as the initial acid washing product.

[0146] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 20wt% and a temperature of 100℃ for 7 hours, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0147] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0148] The sodium-ion battery anode hard carbon material obtained in Example 8 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1, and the cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Example 8 at a high current density of 2 A / g was tested. Figure 17 As shown, Example 8 uses medium-low temperature pyrolysis (900℃) and standard acid washing to produce a coin cell with a specific capacity of approximately 326 mAh / g, demonstrating a feasible process window with performance between low-temperature ultra-high capacity and high-temperature simplified process.

[0149] Comparative Example 1:

[0150] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0151] (2) The wind turbine blade powder was heated to 1200°C in a conventional tube furnace filled with argon at a heating rate of 5°C / min for pyrolysis and carbonization, and held at this temperature for 2 hours. Then it was naturally cooled to room temperature to obtain a hard carbon mixture.

[0152] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 20wt% and a temperature of 60℃ for 12h, then washed with water until the pH value was greater than 6, and filtered to obtain filter residue as the initial acid washing product.

[0153] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 25wt% and a temperature of 120℃ for 6 hours, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0154] (5) The secondary pickling product is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0155] The sodium-ion battery anode hard carbon material obtained in Comparative Example 1 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1. The cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Comparative Example 1 at a high current density of 2 A / g was tested. Figure 18 As shown, Comparative Example 1 uses conventional slow heating and long-term holding without Joule heating for carbonization, and the specific capacity of the resulting coin cell (approximately 234 mAh / g) is much lower than that of all other examples, demonstrating that the Joule heating rapid heating and short-term holding used in this disclosure are crucial for forming a high-performance and unique microstructure.

[0156] Comparative Example 2:

[0157] (1) The wind turbine blades with painted surfaces are cut into pieces with a size of less than 20mm using a cutting machine and then crushed using a crusher. They are then ball-milled at 400rpm for 6h in a planetary ball mill and sieved through an 80-mesh sieve to obtain wind turbine blade powder.

[0158] (2) The wind turbine blade powder was rapidly heated to 1200℃ in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0159] (3) The hard carbon mixture is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain a sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0160] The sodium-ion battery anode hard carbon material obtained in Comparative Example 2 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1. The cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Comparative Example 2 at a high current density of 2 A / g was tested. Figure 19 As shown, Comparative Example 2 completely omitted the acid washing step after Joule pyrolysis, and the specific capacity of the resulting coin cell (approximately 243 mAh / g) was significantly lower, indicating that the acid washing step is essential for removing metallic impurities from wind turbine blades.

[0161] Comparative Example 3:

[0162] (1) Using conventional glucose (i.e. sucrose) as the carbon source, the wind turbine blade powder was obtained by ball milling at 400 rpm for 6 hours in a planetary ball mill and then sieving through an 80-mesh sieve.

[0163] (2) The wind turbine blade powder was rapidly heated to 1200℃ in a Joule heating device filled with argon gas for pyrolysis and carbonization, held at the temperature for 10 minutes, and then naturally cooled to room temperature to obtain a hard carbon mixture.

[0164] (3) The hard carbon mixture was heated and soaked in hydrofluoric acid with a concentration of 20wt% and a temperature of 60℃ for 12h, then washed with water until the pH value was greater than 6, and filtered to obtain filter residue as the initial acid washing product.

[0165] (4) The initial pickling product is heated and soaked in hydrochloric acid with a concentration of 25wt% and a temperature of 120℃ for 6 hours, then washed with water until the pH value is greater than 6, and filtered to obtain filter residue, which is used as the secondary pickling product, namely the battery negative electrode hard carbon material.

[0166] (5) The hard carbon mixture is placed in a high-energy ball mill at 800 rpm, clockwise for 15 minutes, paused for 5 minutes, and then counterclockwise for 15 minutes. This cycle is repeated 8 times to obtain a sodium-ion battery negative electrode hard carbon material with a particle size of less than 300 mesh.

[0167] The sodium-ion battery anode hard carbon material prepared in Comparative Example 3 was used to prepare sodium-ion button batteries using the fabrication method mentioned in Example 1. The cycle performance of the sodium-ion button batteries prepared with the hard carbon material of Comparative Example 3 at a high current density of 2 A / g was tested. Figure 20 As shown, Comparative Example 3 uses a conventional carbon source other than wind turbine blades. The resulting coin cell has an extremely low specific capacity, only about 116 mAh / g after 100 cycles, which strongly demonstrates that the wind turbine blade waste used in this disclosure as a precursor can form a high-performance hard carbon structure with unique sodium ion storage sites that cannot be obtained from conventional carbon sources.

[0168] The above embodiments are merely illustrative of the principles and effects of this disclosure and are not intended to limit this disclosure. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of this disclosure. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in this disclosure should still be covered by the protection scope of this disclosure.

Claims

1. A method for preparing hard carbon material for battery negative electrodes using wind turbine blades, characterized in that, include: A carbonization treatment is performed on wind turbine blade powder to obtain a hard carbon mixture; wherein the wind turbine blade powder is powder formed by crushing glass fiber reinforced resin blades; the carbonization treatment includes: subjecting the wind turbine blade powder to Joule heating treatment under an inert atmosphere; the heating temperature of the Joule heating treatment is 900-1600℃; and The hard carbon mixture is acid-washed to remove impurities, thereby obtaining a battery negative electrode hard carbon material. The acid washing process includes: acid washing the hard carbon mixture with a first acid solution to remove silicon dioxide, thereby obtaining a preliminary acid-washed product; and acid washing the preliminary acid-washed product with a second acid solution to remove metallic impurities, thereby obtaining the battery negative electrode hard carbon material.

2. The method according to claim 1, characterized in that, The first acid solution is a hydrofluoric acid solution, wherein the concentration of the hydrofluoric acid is 8-40 wt%, the temperature is 40-80℃, and the time is 6-24 h.

3. The method according to claim 1, characterized in that, The second acid solution is a hydrochloric acid solution, wherein the concentration of the hydrochloric acid is 12-37 wt%, the temperature is 80-120℃, and the time is 4-12 h.

4. The method according to claim 1, characterized in that, The heating time for the Joule heating treatment is 5-10 minutes.

5. The method according to claim 1, characterized in that, The particle size of the powder in the wind turbine blade powder is less than 80 mesh.

6. The method according to claim 1, characterized in that, Also includes: The battery negative electrode hard carbon material is processed to the micron level and below using high-energy ball milling.

7. The method according to claim 6, characterized in that, The high-energy ball milling process includes: using a high-energy ball mill to ball mill the battery negative electrode hard carbon material at a speed of 800-1000 rpm for 30 minutes, and repeating the cycle 8-12 times.

Citation Information

Patent Citations

  • Method for rapidly preparing hard carbon negative electrode material from waste wind power blade, obtained product and application

    CN119976801A

  • Abandoned wind turbine blade-based porous carbon as well as preparation method and application thereof

    CN120698458A